Season-long comparison of trap lures for integrated management of the navel orangeworm (Lepidoptera: Pyralidae) in almond and pistachio - Joel P. Siegel; Charles S. Burks; Houston Wilson (CABI Agriculture and Bioscience)
Abstract Monitoring navel orangeworm, Amyelois transitella (Lepidoptera: Pyralidae) using pheromone lures is now complicated by the use of mating disruption. Two commercially available lures that are minimally affected by mating disruption use either natural ovipositional substrates (Bait lures) or a combination of phenyl propionate (PPO), a volatile chemical that attracts both sexes and pheromone lures (Combo lures). We compared the season-long trap capture for these two lures in a sterile insect technique (SIT) demonstration project in Fresno County, California, 2020–2023. A total of 194,233 males (96.52%) were caught using Combo lures and 7006 (3.48%) caught using Bait lures, while 95,947 females (48.83%) were caught using Combo lures and 100,532 (51.17%) caught using Bait lures. Capture of A. transitella was 2.3-fold higher in pistachio (278,492) than in almond (119, 316), and within a commodity, there was a moderate correlation in female capture between the two lures; correlation was stronger during the period leading up to July 21 (Julian date 202). For Bait lures, 48.7% of the trap catch in almond occurred by July 21 and 87.1% of the trap catch occurred in pistachio by July 21. For Combo lures, 38.9% of the trap catch in almond occurred by July 21 while 54.6% of the catch occurred in pistachio. Bait lures became less effective after July 21, likely due to diminished attractiveness as new crop nuts split in August through October. Our data indicate that Combo lures are preferable when the goal is consistent season-long capture of A. transitella in almond and pistachio.